2012
DOI: 10.1002/gps.3864
|View full text |Cite
|
Sign up to set email alerts
|

Dementia care costs and outcomes: a systematic review

Abstract: Key points• There is more cost-effectiveness evidence on pharmacological therapies than other interventions. Acetylcholinesterase inhibitors for mild-tomoderate disease and memantine for moderate-to-severe disease were found to be cost-effective.• Regarding non-pharmacological treatments, cognitive stimulation therapy, tailored activity programme and occupational therapy were found to be more cost-effective than usual care. 2• There was some evidence to suggest that respite care in day settings and psychosocia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
135
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 115 publications
(139 citation statements)
references
References 34 publications
2
135
0
2
Order By: Relevance
“…11,23 This study examined the impact of the PDC intervention on VHA health care costs. In our study, the model-adjusted costs for veterans receiving the PDC intervention were not significantly higher than those for the veterans in the control arm, while, as we have documented elsewhere, veterans and their caregivers receiving PDC showed improvements in care outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,23 This study examined the impact of the PDC intervention on VHA health care costs. In our study, the model-adjusted costs for veterans receiving the PDC intervention were not significantly higher than those for the veterans in the control arm, while, as we have documented elsewhere, veterans and their caregivers receiving PDC showed improvements in care outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The literature on cost savings of non-pharmacologic therapies, including those focusing on organization of care, is relatively small and inconclusive. 10,11 Past studies of interventions attempting to better coordinate and manage dementia care have shown mixed impacts on use of services. 12 Fewer studies have focused on health care costs.…”
Section: Introductionmentioning
confidence: 99%
“…Acetyl cholinesterase inhibitors for mild-to-moderate disease and NMDA receptor antagonists (memantine) for moderate-tosevere disease have been found to be cost-effective. 278 Among the non-pharmacological interventions, cognitive stimulation therapy, tailored activity programmes and occupational therapy were found to be more cost-effective than usual care. There is also 82 83 some evidence to suggest that respite care in day settings and psychosocial interventions for carers could be cost-effective.…”
Section: Cost-effectiveness Issuesmentioning
confidence: 99%
“…There is also 82 83 some evidence to suggest that respite care in day settings and psychosocial interventions for carers could be cost-effective. 278 Projections of long term care needs for patients with dementia and associated expenditure have shown that relatively small changes in the prevalence rates of functional disability can have a substantial impact on future expenditure. 279 Based on epidemiological models, there is indication that investing in cost effective public health and management of chronic conditions measures that reduce disability or slow down the progression of dementia may produce good returns in terms of reducing the future costs of long term care.…”
Section: Cost-effectiveness Issuesmentioning
confidence: 99%
“…The National Institute for Health and Care Excellence (NICE) recognises that psychological therapy for dementia family carers should be a key component of high-quality dementia care: 20 'Carers of people with dementia who experience psychological distress and negative psychological impact should be offered psychological therapy, including cognitive-behavioural therapy, conducted by a specialist practitioner' (p. 40). However, the report noted the paucity of evidence in this area, and recommended that research is needed to address the question: 'For carers of people with dementia, is a psychological intervention cost-effective when compared with usual care?'…”
Section: Delivery Of Therapymentioning
confidence: 99%